PENGEMBANGAN SISTEM DETEKSI TANTRUM REAL-TIME BERBASIS IOT UNTUK MENDUKUNG PENDIDIKAN INKLUSIF DI SEKOLAH LUAR BIASA - Sindoro, Nayla Deffonda; Dianti, Sri; Saefullah, Reikhan; Syamsudin, Muhammad Syafri (Educational Technology Journal, 2025)
In Special Education Schools (SLB), detecting and handling negative emotional behaviors such as tantrums in autistic students is a major challenge that directly affects the safety and quality of learning. This study aims to design a real-time tantrum detection system based on the Internet of Things (IoT), integrating a heart rate sensor and a sound sensor, processed using an ESP32 microcontroller and connected to a web-based monitoring platform as a notification medium for teachers. Through a software engineering approach and literature review of over 40 reputable scientific publications, this system is developed as an innovative and applicable early solution in the context of inclusive education. Theoretical reviews indicate that physiological and vocal behavioral indicators are key signals in detecting stress or emotional outbursts in students with Autism Spectrum Disorder (ASD). This system design is expected to contribute to creating a more adaptive, safe, and responsive learning environment in SLB.